2017
DOI: 10.1159/000468996
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor for In-Hospital Mortality in Spontaneous Intracerebral Hemorrhage

Abstract: Health Stroke Scale [NIHSS] 18 [9-32] vs. 10 [4-21]; p < 0.001), larger hematoma volume on admission (17.6 [6.9-47.7] vs. 10.6 [3.8-31.7] mL; p = 0.001), and more frequently unfavorable outcome 116/641; p < 0.001), and increased c-reactive-protein levels on admission ( p < 0.001; R 2 = 0.064). Adjusting for the abovementioned baseline confounders, multivariable logistic analyses revealed independent associations of NLROA with inhospital mortality (OR 0.967, 95% CI 0.939-0.997; p = 0.029). Conclusions: NLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 41 publications
6
102
0
Order By: Relevance
“…These data indicate that the peripheral cellular immune system changed dramatically in the immediate aftermath of ICH. Conversely, the systemic cellular and molecular immune response might also influence local immune response in the hematoma and the outcome of patients with ICH . Although DCs, M/MΦ, neutrophils, lymphocytes (Treg cells, Th17 cells, TCRγδ T cells, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that the peripheral cellular immune system changed dramatically in the immediate aftermath of ICH. Conversely, the systemic cellular and molecular immune response might also influence local immune response in the hematoma and the outcome of patients with ICH . Although DCs, M/MΦ, neutrophils, lymphocytes (Treg cells, Th17 cells, TCRγδ T cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that pro‐inflammatory cells (Th cells, M1 M/MΦ), cytokines (IL‐17, IL‐23), anti‐inflammatory cells (Treg cells, M2 M/MΦ), and cytokines (IL‐4, IL‐10, TGF‐β) participate in the inflammatory response . Studies also show that changes in the cellular and molecular immune system are associated with ICH outcomes . Although previous studies have suggested a relationship between neutrophil‐to‐lymphocyte ratio or white blood cell count and the prognosis of patients with ICH, no study has explored the relationship between ICH severity/outcomes and the systemic and local response of the cellular and molecular immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Yet accounting for sepsis would rather benefit the cancer patient group and this therefore supports the conclusion of our study. A possible reason why an additional cancer diagnosis does not impact long-term prognosis after ICH relates to the severity of the bleeding itself, as demonstrated previously [3,24,32,33,34]. Therefore, the intuitive prognostication that ICH patients with cancer show worse outcomes needs a strong counterbalance to avoid early treatment restrictions and thus self-fulfilling prophecies [12,35].…”
Section: Discussionmentioning
confidence: 90%
“…The NLR increases with time in the first few days. Many previous studies [26][27][28]34] suggested that NLR increases within 12 h after onset and reaches the peak levels the second day. Accurately determining the optimal time to test requires additional research.…”
Section: Figurementioning
confidence: 94%